A kid's guide to how trees grow - Ayers, Patricia (New York : Rosen Pub. Group's PowerKids Press, 1999)
Describes the basics of how different types of trees grow.
13
Keywords: Trees, Care of -- Juvenile literature; Trees -- Juvenile literature; Trees